In vitro susceptibility of Pseudomonas sp. isolated from freshwater fish to antimicrobial agents - Samal, S K; Das, B K; Ghosh, S; Sahu, Swagatika (Indian Journal of Fisheries, 2016)
Ten species of Pseudomonas isolated from healthy and diseased fish species such as catla (Catla catla), rohu (Labeo rohita), mrigal (Cirrhinus mrigala), goldfish (Carassius auratus), climbing perch (Anabas testudineus) and magur (Clarias batrachus) were evaluated for susceptibility to a battery of antimicrobial agents. The bacterial species used for testing were Pseudomonas putida, P. aeruginosa, P. vesicularis, P. syringae, P. pickettii, P. compranosoris, P. alkaligenes, P. fluorescens, P. stutzeri and P. carboxydoflava. The bacteria were screened for susceptibility to 31 antimicrobial agents by the Bauer Disc diffusion method. Most of the bacteria were found susceptible to oxytetracycline, gentamycin, tobramycin, amikacin, ceftriaxone, netillin, tetracycline, and amoxycillin. Majority of the Pseudomonas spp. tested were resistant to cephotaxime, cephalexin, cotrimoxazole, chloramphenicol, nalidixic acid, furazolidone, norfloxacin, augmentin, fluconazole, clotrimazole, cefoxilin, cephalothin, carbenicillin, ceftazidime, piperacillin, tricarcillin, amphotericin-B, cloxacillin and cefuruxime. Testing of the bacterial pathogens belonging to the genus Pseudomonas against gentamycin, oxytetracycline, norfloxacin, tetracycline and amikacin gave larger zones of inhibition on agar plates indicating their usefulness against Pseudomonads’ disease outbreak.